https://doi.org/10.36873/ PERTUMBUHAN DAN HASIL BAWANG DAYAK (Eleutherine americana (L) Merr) YANG DIBERI EMPAT JENIS KOTORAN TERNAK PADA TANAH GAMBUT DAN SPODOSOL: The Growth And Yield Dayak Onion (Eleutherine americana (L) Merr) Fertilized ByFour Kinds Of Manure On Peat And Spodosol - Sih Winarti; Zafrullah Damanik; Rentihen Penyang (Fakultas Pertanian Universitas Palangka Raya, 2021)
The purpose of this study was to determine the growth and yield of dayak onion fertilized by four kind of manure on peat and spodosol. This experiment used a factorial completely randomized design, consisting of two treatment factors with four replications. The treatments were the types of fertilizer (poultry, swallow, cow, goat) and soil types (spodosol, peat). The results showed that growth of plant height, fresh weight, number of tubers, tuber diameter of dayak onion plants that were given chicken manure, swallow manure, cow manure, and goat manure were relatively the same, only the number of leaves that were given cow manure was significantly higher. Onion plants dayak planted on spodosol soil grew better, i.e. taller plants, more number of leaves and number of tubers, larger tuber diameter and fresh weight than those planted on peat soil